Comparative Analysis of Neospora caninum Isolation Success from Various Fetal Tissues: The Importance of Brain Samples. Technical note - Balevi, Asli; Padron, Beatriz; Ilban, Aysegul; Celik, Figen; Toslak, Emine Eda; Denizli, Oguzhan; Simsek, Sami (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Isolating Neospora caninum from naturally infected hosts is crucial for understanding the epidemiology of neosporosis. Although the parasite was reported to be isolated from various fetal tissues, including the brain, the relative successful isolation rates from different sources have not been systematically explored. This study examines the rates of isolating N. caninum from different fetal tissues, focusing on the importance of brain samples. Fetal tissues from 90 naturally infected sheep were analyzed for the presence of N. caninum. Samples were processed for molecular and cell culture isolation techniques. Tachyzoite yields and cytopathogenic effects (CPE) were compared across tissues following isolation in Vero cells. Of the 90 samples, 19 (21.1%) were positive for N. caninum by PCR, and 8 (42.1%) of these yielded viable isolates. Sheep brain tissue exhibited significantly higher tachyzoite yields (1.9 x 107) compared to other tissues (abomasal contents, kidney, placenta, liver and pericardial fluid). The greatest CPE effect at 80% was observed in the eighth passage. Brain samples appear to be the most reliable source for in vitro isolation of N. caninum from naturally infected fetuses. This finding has important implications for the diagnosis and study of sheep neosporosis.
Análisis comparativo del éxito del aislamiento de Neospora caninum a partir de diversos tejidos fetales: la importancia de las muestras cerebrales. Nota técnica
Keywords: Abortion; brain; Neospora caninum; sheep; tissue culture isolation